REVISION OF THE SCLERACTINIAN CORAL GENUS DIPLOCOENIA AND RE-DESCRIPTION OF THE CRETACEOUS SPECIES (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
The Cretaceous species of the coral genus Diplocoenia are revised, mainly on the basis of sample material. This genus is characterised by polygonal calices in a cerioid arrangement, compact septa in a regular symmetry and a dissepimental ring with the appearance of a second inner wall. Of the 18 Cretaceous species reported in the literature, five are confirmed, four are synonyms and nine do not belong to this genus. The species with the widest geographic and stratigraphic distribution is Diplocoenia dollfusi Prever, 1909, originally described from the Monti d’Ocre complex in the Abruzzi region. The genus occurs in the Cretaceous only in the central Tethys and in the Boreal, and ranges from the Middle Jurassic to the Aptian (?early Albian). Only about 50 samples from the Cretaceous exist or are known from the literature, making Diplocoenia rather rare in the Cretaceous.
Keywords: Scleractinian corals; Diplocoenia; Cretaceous; Species redescription; Italy